From educational experiment to standard bearer : University 101 at the University of South Carolina - Friedman, Daniel B.; Skipper, Tracy L. (Tracy Lynn); Greene, Catherine S. (The University of South Carolina Press, 2022)
"An exploration of the University of South Carolina's trailblazing approach to the first-year experience. As an innovative educational experiment, University 101 was designed to support students' transition to and success in college. Now, fifty years after its inception, the program continues to bring national recognition to the University of South Carolina. From Educational Experiment to Standard Bearer celebrates this milestone by exploring the course's origins; its evolution and success at the university; its impact on first-year students, upper-level students serving as peer leaders, faculty and staff instructors, and the university community and culture; and its role in launching the international first-year experience movement. By highlighting the most significant takeaways, lessons learned, and insights to practitioners on other campuses, this book will serve as an inspiration and road map for other institutions to invest in this proven concept and focus on the ingredients that lead to a successful program. John N. Gardner, founding director and architect of University 101, provides a foreword"--